What are the key dimensions of organizational culture? Evidence from Indonesia - Johannes Buntoro Darmasetiawan; Rapina Rapina (People and Behavior Analysis, 2023)
Corporate culture will create peer pressure that will guide the behavior of organization members so that they will work with the same rhythm. The corporate culture is usually influenced by Top Management or by a charismatic founder, who the Top Management still decides to use his/ her ideas. The corporate culture itself is an abstract form; it is difficult to explain what kind of characteristics (colors) it has. Luckily, the "colors" of corporate culture can be described by its dimension. This research introduces ten dimensions that can describe the "color" of corporate culture. This study had 52 participants, and after data processing, it can be stated that Top Management may have a certain belief or tendency that is explained by several dimensions. This means some of the dimensions are correlated to a certain Top Management's belief. Hence, the ten dimensions can be squeezed into less number of dimensions.